Pengaruh Bisnis Digital dalam Konteks e-Commerce Terhadap Pasar Bisnis UMKM Di Masa Pandemi Covid-19 - Mira Fathila Sari; Muhammad Irwan Padli Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the current era of free trade and economic globalization, which is characterized by the liberalization of trade and investment, very rapid progress in the fields of communication, information and technology, the dependence between sellers and buyers has greatly increased. Business activities always require space, so it is clear that e-Commerce applications are built on existing technological infrastructure. Many people think e-Commerce is just a website, even though e-Commerce is actually more than that. The concept of e-Commerce is about how to use the internet to do business better and faster. The spread of the Covid-19 virus has resulted in the Indonesian government imposing social restrictions and PSBB which makes it difficult for people to carry out activities outside the home and closes people's access to income to meet their needs or just buy necessities. One of the impacts of Covid-19 is on UMKM business actors, but with the development of the era, the use of e-Commerce has become an option in doing business.